PERAN STIMULUS VERBAL DALAM PEMEROLEHAN KOSAKATA ANAK USIA 6 TAHUN DENGAN HAMBATAN BICARA: KAJIAN BEHAVIORISME - Hestina Novesima Rachmadani; Hasna Dwi Artika; Bivit Anggoro Prasetyo Nugroho (Jurnal PENEROKA, 2026)
This research aims to describe the process of vocabulary acquisition in a six year old child with speech impairment through verbal stimuli provided in daily interactions. The scope of this research focuses on the basic vocabulary forms successfully articulated by the child, as well as the patterns of stimulus, response, and reinforcement that emerge during the communication process. The method used in this research is a case study with a descriptive qualitative approach, based on behaviorism theory to observe how language habits are formed through repeated interactions. Data were obtained through naturalistic observation, interviews with parents and teachers, and a stimulus response checklist containing records of the child's vocabulary utterances. The data analyzed included spontaneous responses, word imitation, and the child's ability to follow simple commands. The results of the study indicate that the child's vocabulary acquisition developed gradually; the child found it easier to articulate words when seeing concrete objects or hearing clear pronunciation examples. Most utterances were still in the form of syllable fragments, but the child demonstrated an effort to imitate the words provided. Positive reinforcement from parents and teachers proved to make the child more confident in repeating the same words. This finding confirms that consistent verbal stimuli can help in the formation of language habits in children with speech delays, as demonstrated by the increased initiative of the child in initiating simple utterances during observation.